Solid-state battery and gas-phase lithium supplementing preparation method thereof

CN123018120APending Publication Date: 2026-10-30CRYSTAL CORE ENERGY (JIAXING) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611097325.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-22
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0007]本申请的一个目的是提供一种固态电池及其气相补锂制备方法,至少用以解决现有技术中固态电池的补锂均匀性和界面兼容性不足,且固态聚合物电解质在循环过程中产生的裂纹难以修复的技术问题

Benefits of technology

[0019]综上,本申请的固态电池中,固态聚合物电解质层设置于正极和负极之间,且该固态聚合物电解质层以含有四重氢键单元的聚合物作为聚合物基体;同时,负极与固态聚合物电解质层的接触界面处设置有含锂界面层。基于上述结构,含锂界面层能够在负极侧界面处补充活性锂,减少首次充放电过程中因界面膜形成而造成的活性锂不可逆损耗,从而有利于提高固态电池的首次库仑效率;含四重氢键单元的聚合物能够通过可逆氢键作用维持固态聚合物电解质层的结构完整性,减轻循环过程中微裂纹对离子传输和界面接触稳定性的影响,从而有利于提升固态电池的循环稳定性。由此,含四重氢键单元的聚合物基体作为固态聚合物电解质层,与气相补锂技术形成的含锂界面层相配合,能够兼顾固态聚合物电解质层的结构稳定性和负极侧接触界面的补锂需求,进而有利于提升固态电池的界面稳定性、首次库仑效率及循环稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123018120A_ABST
    Figure CN123018120A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of solid-state batteries, and provides a solid-state battery and a gas-phase lithium supplementing preparation method thereof.The solid-state battery comprises an encapsulation shell, a positive electrode, a negative electrode and a solid-state polymer electrolyte layer arranged in the encapsulation shell, the solid-state polymer electrolyte layer is arranged between the positive electrode and the negative electrode, and comprises a polymer containing a quadruple hydrogen bond unit;the negative electrode has a lithium-containing interface layer at the contact interface of the negative electrode and the solid-state polymer electrolyte layer.The lithium-containing interface layer can reduce the irreversible loss of active lithium in the first charge-discharge process, and the polymer containing the quadruple hydrogen bond unit can maintain the structural integrity of the solid-state polymer electrolyte layer, thereby facilitating the improvement of the interface stability, the first coulomb efficiency and the cycle stability of the solid-state battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of solid-state battery technology, and in particular to a solid-state battery and a method for preparing it by vapor-phase lithium replenishment. Background Technology

[0002] Solid-state lithium batteries are considered a key development direction for next-generation energy storage devices due to their high energy density and safety. However, the commercial application of solid-state lithium batteries still faces the following two challenges:

[0003] On the one hand, solid electrolytes are prone to microcracks during cycling. Specifically, solid polymer electrolytes are affected by volume changes and internal stress during battery charging and discharging, leading to the formation of microcracks. These microcracks disrupt the structural continuity of the electrolyte, increase the battery's internal resistance, hinder the effective transport of lithium ions, and ultimately cause battery performance degradation and shorten cycle life.

[0004] On the other hand, solid-state lithium batteries have a relatively low initial coulombic efficiency. During the first charge and discharge cycle, the electrode materials, especially the negative electrode materials, are prone to side reactions with the electrolyte, forming a solid electrolyte interphase (SEI) film. This process irreversibly consumes some active lithium and may produce "dead lithium," thereby reducing the battery's initial coulombic efficiency and limiting further improvements in battery energy density.

[0005] Existing publicly available lithium replenishment technologies, such as pre-placed lithium powder and lithium foil, suffer from problems such as uneven distribution, complex processes, or poor interface compatibility with solid-state batteries. Traditional polymer electrolytes typically lack self-healing capabilities, and once cracks occur, performance degradation is difficult to reverse.

[0006] Therefore, there is an urgent need to develop a solid-state battery system that can autonomously repair damage and replenish active lithium in an efficient and uniform manner. Summary of the Invention

[0007] One objective of this application is to provide a solid-state battery and a method for preparing the same in the gas phase, which at least solves the technical problems of insufficient uniformity of lithium replenishment and interface compatibility in the prior art, and the difficulty in repairing cracks generated in the solid polymer electrolyte during cycling.

[0008] To achieve the above objectives, some embodiments of this application provide the following aspects:

[0009] In a first aspect, the present invention provides a solid-state battery, including a package shell and a positive electrode, a negative electrode and a solid polymer electrolyte layer disposed within the package shell; the solid polymer electrolyte layer is disposed between the positive electrode and the negative electrode and includes a polymer containing four hydrogen bond units; the contact interface between the negative electrode and the solid polymer electrolyte layer has a lithium-containing interface layer.

[0010] Secondly, the present invention provides a method for preparing a solid-state battery using vapor-phase lithium replenishment, for preparing the aforementioned solid-state battery. The method includes: sequentially stacking a positive electrode, a solid polymer electrolyte layer, and a negative electrode in a single-layer battery cell structure of positive electrode-solid polymer electrolyte layer-negative electrode and placing them into a packaging shell, retaining a vapor phase inlet opening to obtain a battery assembly to be processed; wherein the solid polymer electrolyte layer comprises a polymer containing quadruple hydrogen bond units; placing the battery assembly to be processed in a vapor-phase processing chamber, and supplying a lithium-containing vapor phase formed by a lithium replenishment agent source to the vapor-phase processing chamber under an inert atmosphere via a supply device, allowing the lithium-containing vapor phase to enter the battery assembly to be processed through the vapor phase inlet opening and diffuse to the contact interface between the negative electrode and the solid polymer electrolyte layer, thereby forming a lithium-containing interface layer at the contact interface; after the lithium-containing vapor phase processing is completed, purging the vapor-phase processing chamber with an inert gas, and then finally packaging the battery assembly to be processed.

[0011] Preferably, the quadruple hydrogen bond unit is a ureidinone unit and / or a ureidinone-derived structural unit, which is capable of forming quadruple hydrogen bond association. The ureidinone unit and / or the ureidinone-derived structural unit can form quadruple hydrogen bonds with high bonding strength and dynamic reversibility, allowing the quadruple hydrogen bond units on both sides of the crack to reassociate. This is beneficial for repairing microcracks in the solid polymer electrolyte layer and maintaining the structural integrity of the electrolyte layer and ion transport channels.

[0012] Preferably, the solid polymer electrolyte layer further includes a functional filler incorporated into the polymer containing quadruple hydrogen bond units. By incorporating the functional filler into the polymer, the mechanical support capability of the solid polymer electrolyte layer can be enhanced, and the structural stability of the solid polymer electrolyte layer can be maintained.

[0013] Preferably, the functional filler comprises nano-silica functionalized with quadruple hydrogen bonding units, and / or nano-aramid fibers. Nano-silica functionalized with quadruple hydrogen bonding units can participate in the construction of a multi-level dynamic hydrogen bond network, enhancing the mechanical support capacity of the solid polymer electrolyte layer while reducing the risk of functional filler migration or detachment; nano-aramid fibers can further improve the tensile strength and dimensional stability of the solid polymer electrolyte layer, which is beneficial for maintaining the uniformity of the solid polymer electrolyte layer's performance.

[0014] Preferably, the lithium replenishing agent source is formed into the lithium-containing gas phase through vaporization, sublimation, atomization, and thermal decomposition, or it is formed by being carried by a carrier gas. Selecting the appropriate gas phase formation method based on the morphology and thermophysical properties of the lithium replenishing agent source allows the lithium-containing material to enter the gas phase processing chamber in a transportable gas phase or gas-carrying state, which is beneficial for improving the adaptability of the gas phase lithium replenishment process.

[0015] Preferably, the lithium replenishment source includes any one or a mixture of at least two of tert-butyllithium, a complex formed from lithium and a low-boiling-point ether, and low-molecular-weight lithium carboxylate. By selecting different types of lithium replenishment sources, a suitable lithium replenishment scheme can be chosen according to the lithium replenishment activity, processing temperature, and safety requirements.

[0016] Preferably, in the complex formed by lithium and the low-boiling-point ether, the low-boiling-point ether includes tetrahydrofuran and / or dimethoxyethane. Using a low-boiling-point ether to form the complex facilitates the formation of a transportable lithium-containing gas phase under milder processing conditions, reducing the impact of the gas-phase lithium replenishment process on the thermal stability of the battery module.

[0017] Preferably, the low molecular weight lithium carboxylate includes lithium formate and / or lithium acetate. Using lithium formate and / or lithium acetate as a lithium replenishment source is beneficial for improving the storage stability and operational safety of the lithium replenishment source, and provides an optional lithium source for gas-phase lithium replenishment.

[0018] Preferably, the lithium replenishment source is a tert-butyllithium / pentane solution. The tert-butyllithium / pentane solution is prepared through the following steps: under inert gas protection, a lithium metal dispersion is added to pentane, and a reaction solution containing chlorinated n-butane is added dropwise under stirring at 35°C to obtain a reactant; the reactant is filtered, washed, and diluted to obtain a 1.0 mol / L tert-butyllithium / pentane solution; in the gas-phase lithium replenishment method, the tert-butyllithium / pentane solution is vaporized, atomized, or carried by a carrier gas to form the lithium-containing gas phase. Using a tert-butyllithium / pentane solution with a clearly defined composition and concentration as the lithium replenishment source is beneficial for controlling the supply amount of lithium-containing active components; forming a lithium-containing gas phase through vaporization, atomization, or carrier gas carrying allows for selection of the appropriate supply method based on the gas phase processing equipment and safety control conditions, thereby improving the controllability and repeatability of the gas-phase lithium replenishment process.

[0019] In summary, in the solid-state battery of this application, a solid polymer electrolyte layer is disposed between the positive and negative electrodes, and this solid polymer electrolyte layer uses a polymer containing four hydrogen bond units as the polymer matrix; simultaneously, a lithium-containing interface layer is disposed at the contact interface between the negative electrode and the solid polymer electrolyte layer. Based on the above structure, the lithium-containing interface layer can replenish active lithium at the negative electrode side interface, reducing the irreversible loss of active lithium caused by the formation of the interface film during the first charge and discharge process, thereby improving the first coulombic efficiency of the solid-state battery; the polymer containing four hydrogen bond units can maintain the structural integrity of the solid polymer electrolyte layer through reversible hydrogen bonding, reducing the impact of microcracks on ion transport and interface contact stability during cycling, thereby improving the cycle stability of the solid-state battery. Therefore, the polymer matrix containing four hydrogen bond units as the solid polymer electrolyte layer, combined with the lithium-containing interface layer formed by the gas-phase lithium replenishment technology, can take into account both the structural stability of the solid polymer electrolyte layer and the lithium replenishment requirements of the negative electrode side contact interface, thus improving the interface stability, first coulombic efficiency, and cycle stability of the solid-state battery.

[0020] In the solid-state battery vapor-phase lithium replenishment method of this application, after the positive electrode, solid polymer electrolyte layer, and negative electrode are stacked sequentially and packaged, a vapor phase inlet is retained. Before final packaging, a lithium-containing vapor phase formed by the lithium replenishment agent source is introduced into the battery assembly to be treated through the vapor phase inlet, further diffusing to the contact interface between the negative electrode and the solid polymer electrolyte layer to form a lithium-containing interface layer at the contact interface. Since the lithium-containing vapor phase can enter the battery assembly to be treated before packaging and act on the target contact interface, the targeting of the lithium replenishment location and the uniformity of interface lithium replenishment can be improved. At the same time, the polymer containing four hydrogen bond units serves as the polymer matrix of the solid polymer electrolyte layer, which can maintain the structural integrity of the solid polymer electrolyte layer. Combined with the lithium-containing interface layer formed by the vapor-phase lithium replenishment, it is beneficial to improve the interface stability, initial coulombic efficiency, and cycle stability of the solid-state battery. After vapor phase treatment, inert gas is used for purging and final packaging, which can reduce the impact of residual vapor phase substances on battery packaging and subsequent electrochemical performance. Attached Figure Description

[0021] Figure 1 This is a schematic diagram of the layered structure of a solid-state battery provided in an embodiment of the present invention;

[0022] Figure 2 This is a flowchart of the solid-state battery preparation method for gas-phase lithium replenishment provided in an embodiment of the present invention.

[0023] Figure reference numerals: 10-Solid-state battery; 11-Encapsulation shell; 12-Positive electrode; 13-Negative electrode; 14-Solid polymer electrolyte layer; 15-Polymer containing quadruple hydrogen bond units; 16-Lithium-containing interface layer. Detailed Implementation

[0024] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.

[0025] Unless otherwise stated, the technical terms used in this application have the meanings commonly understood by those skilled in the art; the raw materials, equipment and testing methods in each embodiment can all be sourced from or equipped with conventional equipment in the art.

[0026] like Figure 1 As shown, this application provides a solid-state battery 10, which includes a package shell 11 and a positive electrode 12, a negative electrode 13 and a solid polymer electrolyte layer 14 disposed within the package shell 11; the solid polymer electrolyte layer 14 is disposed between the positive electrode 12 and the negative electrode 13 and includes a polymer 15 containing four hydrogen bond units; the contact interface between the negative electrode 13 and the solid polymer electrolyte layer 14 has a lithium-containing interface layer 16.

[0027] The positive electrode 12 can be a lithium nickel cobalt manganese oxide (NCM) positive electrode sheet or other positive electrode structures suitable for solid-state batteries, and the negative electrode 13 can be a graphite negative electrode sheet or other negative electrode structures capable of inserting and extracting lithium ions. The polymer 15 in the solid polymer electrolyte layer 14 serves as the polymer matrix, and its main chain and / or side chains can be provided with quadruple hydrogen bond units to form a dynamic reversible hydrogen bond network. A quadruple hydrogen bond unit refers to a structural unit capable of forming multi-point reversible hydrogen bond association between polymer molecular chains, and it can be located on the polymer's main chain and / or side chains.

[0028] A lithium-containing interface layer 16 is disposed at the contact interface between the negative electrode 13 and the solid polymer electrolyte layer 14. In some embodiments, the lithium-containing interface layer 16 may cover at least a portion of the contact interface and may include lithium-containing reaction products formed after the lithium-containing active component interacts with the surface of the negative electrode 13, the surface of the solid polymer electrolyte layer 14, and / or interface defects. The lithium-containing interface layer 16 may be formed in the gas-phase lithium replenishment preparation method described later and exists as the final interface structure in the solid-state battery 10.

[0029] Based on the above structure, the lithium-containing interface layer 16 can replenish active lithium at the contact interface, reducing the irreversible loss of active lithium caused by the formation of the interface film during the first charge and discharge process, thereby improving the first coulombic efficiency of the solid-state battery 10. The polymer 15 containing quadruple hydrogen bond units can maintain the structural integrity of the solid polymer electrolyte layer 14 through reversible hydrogen bonding, reducing the impact of microcracks on ion transport and interface contact stability during cycling, thereby improving the cycle stability of the solid-state battery 10. Thus, the polymer 15 containing quadruple hydrogen bond units, as the polymer matrix of the solid polymer electrolyte layer 14, works in conjunction with the lithium-containing interface layer 16 to balance the structural stability of the solid polymer electrolyte layer 14 and the lithium replenishment requirements at the contact interface, thereby improving the interface stability, first coulombic efficiency, and cycle stability of the solid-state battery 10.

[0030] Optionally, in some embodiments, the quadruple hydrogen bond unit is a ureidinone unit and / or a ureidinone-derived structural unit, which is capable of forming a quadruple hydrogen bond association.

[0031] Specifically, ureidinone units and / or ureidinone-derived structural units can be disposed on the main chain and / or side chain of polymer 15. The ureidinone-derived structural units can be structural units formed by adjusting substituents or linking groups based on ureidinone units, and can form quadruple hydrogen bond association. The ureidinone units and / or the ureidinone-derived structural units can undergo reversible dissociation and reassociation, causing the hydrogen bond units on both sides of the microcracks within the solid polymer electrolyte layer 14 to re-pair, thereby repairing the microcracks and maintaining the structural integrity of the solid polymer electrolyte layer 14.

[0032] Since the ureidopyrimidinone unit and / or the ureidopyrimidinone-derived structural unit can form quadruple hydrogen bonds with high bonding strength and dynamic reversibility, when the solid polymer electrolyte layer 14 generates microcracks due to volume changes or internal stress during charging and discharging, the quadruple hydrogen bond units on both sides of the crack can reassociate, which helps to reduce the risk of structural damage and interface impedance growth caused by the continuous propagation of microcracks.

[0033] Optionally, in some embodiments, the solid polymer electrolyte layer 14 further includes a functional filler incorporated into the polymer 15 containing quadruple hydrogen bond units.

[0034] Specifically, the functional filler can be dispersed, embedded, or compounded in the polymer matrix formed by the polymer 15 to jointly constitute the solid polymer electrolyte layer 14 with the polymer 15. The functional filler can provide mechanical support for the solid polymer electrolyte layer 14 and reduce local deformation caused by volume changes and internal stress during cycling.

[0035] By incorporating functional fillers into polymer 15 containing quadruple hydrogen bond units, the mechanical support capacity of solid polymer electrolyte layer 14 can be enhanced, and the structural stability of solid polymer electrolyte layer 14 can be maintained.

[0036] Optionally, in some embodiments, the functional filler comprises nano-silica and / or nano-aramid fibers functionalized with quadruple hydrogen bonding units.

[0037] Specifically, the nano-silica functionalized with quadruple hydrogen bonding units can form reversible hydrogen bonds with the quadruple hydrogen bonding units in polymer 15, thereby improving the interfacial bonding strength between the nano-silica and the polymer matrix. Nano-aramid fibers can further improve the tensile strength and dimensional stability of the solid polymer electrolyte layer 14.

[0038] Therefore, nano-silica functionalized with quadruple hydrogen bond units can participate in the construction of a multi-level dynamic hydrogen bond network, which enhances the mechanical support capability of the solid polymer electrolyte layer 14 while reducing the risk of filler migration or detachment; nano-aramid fibers can further improve the mechanical stability of the solid polymer electrolyte layer 14, which is conducive to maintaining the uniformity of the performance of the solid polymer electrolyte layer 14.

[0039] This application also provides a method for preparing solid-state batteries using vapor-phase lithium supplementation, such as... Figure 2 As shown, the vapor-phase lithium replenishment method is used to prepare the solid-state battery 10 as described above, and the preparation method includes:

[0040] The positive electrode, the solid polymer electrolyte layer, and the negative electrode are stacked sequentially in a single-layer battery cell structure of positive electrode-solid polymer electrolyte layer-negative electrode and then packaged in a shell, with the gas phase entering the opening, to obtain the battery assembly to be processed. The solid polymer electrolyte layer includes a polymer containing four hydrogen bond units.

[0041] The battery assembly to be treated is placed in a gas phase processing chamber. Under an inert atmosphere, a lithium-containing gas phase formed by a lithium replenishment source is supplied to the gas phase processing chamber through a supply device. The lithium-containing gas phase enters the battery assembly to be treated through the gas phase inlet and diffuses to the contact interface between the negative electrode and the solid polymer electrolyte layer to form a lithium-containing interface layer at the contact interface.

[0042] After the lithium-containing vapor phase treatment is completed, the vapor phase treatment chamber is purged with inert gas, and then the battery assembly to be treated is finally packaged.

[0043] The lithium-containing gas phase can be the gaseous or gas-carried state of lithium-containing active components formed after the lithium replenishment source has undergone vaporization, sublimation, atomization, thermal decomposition, or carrier gas transport. It is not limited to the lithium replenishment source being entirely in gaseous molecular form. The contact interface refers to the solid-solid contact area formed between the surface of the negative electrode 13 facing the solid polymer electrolyte layer 14 and the opposite surface of the solid polymer electrolyte layer 14. The gas phase inlet can be an unsealed area reserved before final encapsulation, an injection port, a gas guiding channel, or other opening structure that allows the lithium-containing gas phase to enter the interior of the battery assembly to be processed.

[0044] Specifically, the vapor phase lithium replenishment step is performed before final packaging, leaving a vapor phase inlet opening in the battery assembly to be treated, allowing the lithium-containing vapor phase to enter the battery assembly and reach the contact interface between the negative electrode 13 and the solid polymer electrolyte layer 14. The inert gas can be argon. After the vapor phase treatment is completed, argon can be used to purge the vapor phase treatment chamber and / or the battery assembly to be treated to remove residual lithium-containing vapor phase, by-product gases, or solvent vapors.

[0045] In one specific implementation, the processing temperature of the lithium-containing gas phase can be controlled at 30–80°C, and the processing pressure in the gas phase processing chamber can be controlled at 0.5–1.5 standard atmospheres.

[0046] Controlling the processing temperature between 30 and 80°C is beneficial for the formation and transport of lithium-containing gas phase and can reduce the risk of adverse effects of high temperature on the solid polymer electrolyte layer 14, the encapsulation shell 11, and the electrode structure. Controlling the processing pressure between 0.5 and 1.5 standard atmospheres is beneficial for maintaining the diffusion stability of the lithium-containing gas phase in the gas phase processing chamber, allowing it to enter the battery assembly to be processed more uniformly and reach the target contact interface.

[0047] In one specific implementation, after the lithium-containing vapor phase treatment is completed and before final packaging, the battery component to be treated can undergo interface activation treatment. The interface activation treatment may include ultraviolet irradiation and / or heating treatment; the ultraviolet irradiation may use ultraviolet light with a wavelength of 365 nm.

[0048] Specifically, ultraviolet irradiation, heating treatment, or a combination of ultraviolet irradiation and heating treatment can be used alone to promote the distribution, reaction, or stabilization of lithium-containing active components at the contact interface between the negative electrode 13 and the solid polymer electrolyte layer 14.

[0049] Performing interface activation treatment before final packaging is beneficial for promoting the distribution of lithium-containing materials at the contact interface and reducing local lithium concentration differences. Using ultraviolet irradiation and / or heating treatment can also select the appropriate activation method according to the activation conditions of the lithium replenishment source and the tolerance conditions of the battery component to be treated.

[0050] Since the lithium-containing gas phase can enter the battery assembly to be processed and act on the target contact interface before final packaging, it can improve the targeting of lithium replenishment sites and the uniformity of interface lithium replenishment. Simultaneously, the polymer 15 containing quadruple hydrogen bonds, serving as the polymer matrix of the solid polymer electrolyte layer 14, can maintain the structural integrity of the solid polymer electrolyte layer 14. Combined with the lithium-containing interface layer 16 formed by gas-phase lithium replenishment, this is beneficial for improving the interface stability, initial coulombic efficiency, and cycle stability of the solid-state battery 10. After gas-phase treatment, purging with inert gas and final packaging can reduce the impact of residual gas phase substances on battery packaging and subsequent electrochemical performance.

[0051] Optionally, in some embodiments, the lithium supplement source is formed by vaporization, sublimation, atomization or thermal decomposition to form the lithium-containing gas phase, or is formed by being carried by a carrier gas.

[0052] Specifically, the appropriate lithium-containing gas phase formation method can be selected based on the physical state, thermal properties, and reactivity of the lithium replenishing agent source. For example, when the lithium replenishing agent source is in a liquid or solution state, vaporization, atomization, or carrier gas carrying methods can be used; when the lithium replenishing agent source is a solid substance that can sublimate or thermally decompose, sublimation, thermal decomposition, or carrier gas carrying methods can be used.

[0053] By selecting the appropriate gas phase formation method based on the morphology and thermophysical properties of the lithium replenishment source, lithium-containing active components can enter the gas phase processing chamber in a transportable gas phase or gas carrier state, which is beneficial to improving the adaptability of the gas phase lithium replenishment process to different lithium replenishment sources.

[0054] Optionally, in some embodiments, the lithium source includes any one or a mixture of at least two of tert-butyllithium, a complex formed by lithium and a low-boiling-point ether, and low-molecular-weight lithium carboxylate.

[0055] Among them, tert-butyllithium can be used as a highly active lithium supplement source; the complex formed by lithium and low-boiling-point ether can form a transportable lithium-containing gas phase under relatively mild conditions; and low molecular weight lithium carboxylate can be used as a lithium supplement source in application scenarios with high requirements for safety and storage stability.

[0056] By selecting different types of lithium replenishment sources, a suitable lithium replenishment scheme can be chosen based on lithium replenishment activity, processing temperature, safety, and equipment conditions.

[0057] Optionally, in some embodiments, the complex formed by the lithium and the low-boiling-point ether includes tetrahydrofuran and / or dimethoxyethane.

[0058] Specifically, the lithium source can form a complex with tetrahydrofuran and / or dimethoxyethane. The complex can then form a transportable lithium-containing gas phase under heating conditions and be supplied to a gas phase processing chamber.

[0059] In one specific implementation, the lithium replenishment source can be a lithium-tetrahydrofuran complex formed by lithium and tetrahydrofuran. The lithium-tetrahydrofuran complex is heated to 45°C to form a lithium-containing gas phase, and the lithium-containing gas phase is transported to a gas phase processing chamber and treated at 1 standard atmosphere for 15 minutes; subsequently, argon gas is used for purging and final encapsulation is completed.

[0060] Using tetrahydrofuran and / or dimethoxyethane as low-boiling-point ethers to form complexes is beneficial for forming a transportable lithium-containing gas phase under milder processing conditions, thereby reducing the impact of the gas phase lithium replenishment process on the thermal stability of the battery components to be processed.

[0061] Optionally, in some embodiments, the low molecular weight lithium carboxylate includes lithium formate and / or lithium acetate.

[0062] Specifically, lithium formate and lithium acetate can be sublimated, thermally decomposed, or carried by a carrier gas to form a lithium-containing gas phase, which is then transported to a gas phase processing chamber for gas phase lithium replenishment of the battery components to be treated.

[0063] In one specific implementation, the container containing lithium acetate can be heated to 60°C, and the resulting lithium-containing gas phase can be introduced into a gas phase treatment chamber and treated at 1.2 standard atmospheres for 15 minutes; lithium formate can be used as a lithium replenishment source instead of lithium acetate.

[0064] Using lithium formate and / or lithium acetate as lithium replenishment sources is beneficial for improving the storage stability and operational safety of lithium replenishment sources, and provides an optional lithium source for gas-phase lithium replenishment.

[0065] Optionally, in some embodiments, the lithium replenishment source is a tert-butyllithium / pentane solution. The tert-butyllithium / pentane solution is prepared by the following steps: under inert gas protection, a lithium metal dispersion is added to pentane, and a reaction solution containing chlorinated n-butane is added dropwise under stirring at 35°C to obtain a reactant; the reactant is filtered, washed, and diluted to obtain a 1.0 mol / L tert-butyllithium / pentane solution; in the gas-phase lithium replenishment method, the tert-butyllithium / pentane solution is vaporized, atomized, or carried by a carrier gas to form the lithium-containing gas phase.

[0066] In one specific implementation, the inert gas can be argon. Pentane can be used as a volatile solvent or carrier medium, allowing the lithium-containing active component of tert-butyllithium to enter the gas-phase processing chamber via vaporization, atomization, or carrier gas transport. The amount of lithium-containing active component supplied to the gas-phase processing chamber can be adjusted by controlling the concentration, supply rate, processing temperature, and processing time of the tert-butyllithium / pentane solution.

[0067] Using a lithium tert-butyllithium / pentane solution with a clearly defined composition and concentration as the lithium replenishment source is beneficial for controlling the supply of lithium-containing active components. By vaporizing, atomizing, or carrying the lithium tert-butyllithium / pentane solution to form a lithium-containing gas phase, the appropriate supply method can be selected according to the gas phase processing equipment and safety control conditions, thereby improving the controllability and repeatability of the gas phase lithium replenishment process.

[0068] Performance test group 1

[0069] In this experimental group, a composite solid polymer electrolyte membrane was prepared using a polymer containing ureidopyrimidinone (UPy) units, lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), and nano-silica filler functionalized with ureidopyrimidinone (UPy) units. Gas-phase lithium replenishment was performed using a tert-butyllithium / pentane solution to verify the performance of the combined scheme.

[0070] A composite solid polymer electrolyte membrane was obtained by dissolving or dispersing a polymer containing UPy units, LiTFSI, and UPy-functionalized nano-silica filler in a solvent, casting the mixture into a film, and then vacuum drying it. The polymer containing UPy units can be a self-healing polymer with UPy units in the main chain and / or side chains. LiTFSI serves as a lithium salt to provide lithium-ion conduction channels, and the UPy-functionalized nano-silica filler enhances mechanical properties and participates in the construction of a dynamic hydrogen bond network.

[0071] NCM positive electrode and graphite negative electrode are prepared. The positive electrode, composite solid polymer electrolyte membrane and negative electrode are stacked in sequence and placed into an aluminum-plastic package, leaving an opening for the lithium-containing gas phase to enter, to obtain the battery assembly to be processed.

[0072] The battery assembly to be processed was transferred to a vapor phase processing chamber, which was then evacuated and filled with argon gas. A tert-butyllithium / pentane solution was supplied via a precision injection system, forming a lithium-containing gaseous state under the influence of argon gas, and slowly introduced into the vapor phase processing chamber. The processing temperature in the vapor phase processing chamber was controlled at 50°C, and the process was carried out at 1 atmosphere for 10 minutes. Afterwards, the vapor phase processing chamber was purged with argon gas to remove residual gaseous substances. Finally, the battery assembly to be processed was encapsulated under vacuum to obtain a solid-state battery 10.

[0073] In this process, the lithium-containing gas phase enters the battery assembly to be treated and reaches the contact interface between the graphite anode sheet and the composite solid polymer electrolyte membrane. It interacts with interface defects or side reaction sites to form a lithium-containing interface layer 16. The lithium-containing interface layer 16 is used to compensate for the active lithium consumed in the formation of the interface film during the first charge and discharge process. The UPy dynamic hydrogen bond network in the composite solid polymer electrolyte membrane is used to repair microcracks and maintain interface contact stability during subsequent cycles.

[0074] Performance test group 2

[0075] This test group is basically the same as the performance test group 1, except that the lithium supplement source is a lithium-tetrahydrofuran complex.

[0076] The container containing the lithium-tetrahydrofuran complex is heated to 45°C to form a lithium-containing gas phase, which is then introduced into the gas phase treatment chamber for gas phase lithium replenishment treatment of the battery assembly to be treated; the treatment pressure is 1 standard atmosphere and the treatment time is 15 minutes.

[0077] The lithium-tetrahydrofuran complex used in this experiment can form a lithium-containing gas phase at a lower temperature. The gas phase lithium replenishment process is relatively mild, which helps to reduce the thermal impact on the solid polymer electrolyte membrane and encapsulation materials.

[0078] Performance test group 3

[0079] This test group is basically the same as the performance test group 1, except that the lithium supplement source is lithium acetate (CH3COOLi).

[0080] In the gas phase lithium replenishment step, lithium acetate is placed in a supply device, carried by argon gas to form a lithium-containing gaseous state, and introduced into the gas phase processing chamber for gas phase lithium replenishment treatment of the battery assembly to be treated; the processing temperature of the gas phase processing chamber is controlled at 60°C, the processing pressure is 1.2 standard atmospheres, and the processing time is 15 minutes.

[0081] In other embodiments, lithium acetate can be replaced with lithium formate (HCOOLi), and a lithium-containing gas phase can be formed by sublimation, thermal decomposition, or carrier gas transport.

[0082] Performance test group 4

[0083] This test group is basically the same as the performance test group 1, except that after the gas phase lithium replenishment is completed and before final packaging, it is activated by irradiation with ultraviolet light with a wavelength of 365nm.

[0084] Ultraviolet irradiation activation is used to promote the distribution and stabilization of lithium-containing materials at the interface between the negative electrode 13 and the solid polymer electrolyte membrane, thereby further improving the uniformity of the lithium-containing interface layer 16.

[0085] Performance test group 5

[0086] This test group is basically the same as the performance test group 1, except that the composite solid polymer electrolyte membrane does not contain UPy-functionalized nano silica filler.

[0087] This experimental group was used to verify the effects of functional fillers on the mechanical support capacity and cycle stability of composite solid polymer electrolyte membranes.

[0088] Comparative Example 1

[0089] The difference between this comparative example and performance test group 1 is that no gas phase lithium replenishment treatment was performed. That is, the battery components to be treated were directly encapsulated after stacking without being processed in the gas phase treatment chamber. Only a composite solid polymer electrolyte membrane was used, and all other conditions were the same as those in performance test group 1.

[0090] Comparative Example 2

[0091] The difference between this comparative example and performance test group 1 is that the polymer containing UPy units is replaced with ordinary polyethylene oxide (PEO) without quadruple hydrogen bond units, while all other conditions are the same as those in performance test group 1.

[0092] Comparative Example 3

[0093] The difference between this comparative example and performance test group 1 is that inert argon gas, which does not provide active lithium, is used instead of lithium-containing gas phase for treatment. That is, the battery module to be treated undergoes the same temperature (50°C), pressure (1 standard atmosphere), and treatment time (10 minutes) as performance test group 1, but the supply gas is pure argon gas instead of lithium-containing gas phase, so as to eliminate the influence of non-specific factors such as temperature, pressure, and airflow on battery performance during gas phase treatment; all other conditions are the same as performance test group 1.

[0094] Comparative Example 4

[0095] The difference between this comparative example and performance test group 1 is that the polymer containing UPy units is replaced with ordinary polyethylene oxide (PEO), and no gas-phase lithium replenishment treatment is performed. All other conditions are the same as those in performance test group 1.

[0096] The solid-state batteries obtained from the above performance test group and the comparative example were tested under the same test conditions. The initial coulombic efficiency and the capacity retention rate after 500 cycles were tested, and the results are shown in Table 1.

[0097] Table 1

[0098] sample First-time coulomb efficiency (%) Capacity retention rate (%) after 500 cycles Performance test group 1 92 90 Performance test group 2 91 89 Performance test group 3 90 88 Performance test group 4 93 91 Performance test group 5 91 86 Comparative Example 1 85 70 Comparative Example 2 90 65 Comparative Example 3 84 72 Comparative Example 4 80 50

[0099] In the initial coulombic efficiency test, the assembled solid-state battery was left to stand at room temperature (25±2℃) for 12 hours before charge-discharge testing. It was charged at a constant current rate of 0.1C to the cutoff voltage; when the positive electrode is NCM material, the cutoff voltage can be set to 4.3V. Subsequently, it was charged at a constant voltage at the cutoff voltage until the current dropped to 0.05C; after standing for 10 minutes, it was discharged at a constant current rate of 0.1C to the cutoff voltage, which can be 2.8V. The initial coulombic efficiency was calculated using the following formula:

[0100] Initial coulombic efficiency (%) = (initial discharge capacity / initial charge capacity) × 100%.

[0101] After the initial coulombic efficiency test, the same solid-state battery underwent long-term cycle testing. The charge / discharge rate was 0.5C / 0.5C; during charging, it was first charged at a constant current of 0.5C to the cutoff voltage, then charged at a constant voltage until the current dropped to 0.05C; during discharging, it was discharged at a constant current of 0.5C to the discharge cutoff voltage; a 10-minute rest period was maintained between each charge / discharge cycle; the test temperature was room temperature (25±2℃); 500 charge / discharge cycles were performed continuously. The capacity retention rate after 500 cycles was calculated using the following formula:

[0102] Capacity retention rate after 500 cycles = (Discharge capacity of the 500th cycle / Discharge capacity of the first cycle) × 100%.

[0103] Table 1 shows that Comparative Example 1, without gas-phase lithium replenishment treatment, and Comparative Example 3, which used argon gas (which does not provide active lithium) to replace the lithium-containing gas phase, achieved initial coulombic efficiencies of 85% and 84%, respectively, and capacity retention rates of 70% and 72% after 500 cycles, respectively. Performance test groups 1–5 all underwent gas-phase lithium replenishment treatment, achieving initial coulombic efficiencies of 90%–93% and capacity retention rates of 86%–91% after 500 cycles. These results indicate that gas-phase lithium replenishment treatment can improve the loss of active lithium at the initial interface and is beneficial for increasing the initial coulombic efficiency.

[0104] Comparative Example 2 used a standard polyethylene oxide (PEO) matrix without quadruple hydrogen bond units and retained the gas-phase lithium replenishment treatment. Its initial coulombic efficiency was 90%, but the capacity retention after 500 cycles was 65%. The results of performance test group 1 and Comparative Example 2 indicate that polymer 15 containing quadruple hydrogen bond units has a positive effect on long-term cycling performance.

[0105] Comparative Example 4 uses a common PEO matrix and has not undergone gas-phase lithium replenishment treatment. Its initial coulombic efficiency is 80%, and its capacity retention rate after 500 cycles is 50%, which is lower than that of performance test groups 1-5.

[0106] The comprehensive performance test group and the comparative example show that the gas phase lithium replenishment treatment mainly improves the active lithium loss and the first coulombic efficiency at the initial interface, while the solid polymer electrolyte containing quadruple hydrogen bond units mainly maintains the structural and interface integrity during long-term cycling. The combination of the two is beneficial to improving the overall performance of solid-state batteries.

[0107] The numerical range described in this application includes the endpoints of the range and any subranges between the endpoints. Unless the context clearly defines it, the term "including" does not exclude the inclusion of other structures or steps, and the singular form also includes the plural case.

[0108] The above embodiments are used to illustrate the technical solutions of the present invention, and are not intended to limit the scope of protection of the present invention. Equivalent substitutions or conventional modifications made by those skilled in the art based on the disclosure of this application without departing from the concept of the present invention should all fall within the scope of protection of the present invention.

Claims

1. A solid-state battery, characterized in that, The device includes a package shell and a positive electrode, a negative electrode, and a solid polymer electrolyte layer disposed within the package shell; the solid polymer electrolyte layer is disposed between the positive electrode and the negative electrode and includes a polymer containing four hydrogen bond units; the interface between the negative electrode and the solid polymer electrolyte layer has a lithium-containing interface layer.

2. The solid-state battery according to claim 1, characterized in that, The quadruple hydrogen bond unit is a ureidopyrimidinone unit and / or a ureidopyrimidinone-derived structural unit, which is capable of forming a quadruple hydrogen bond association.

3. The solid-state battery according to claim 1, characterized in that, The solid polymer electrolyte layer also includes a functional filler, which is incorporated into the polymer containing four hydrogen bond units.

4. The solid-state battery according to claim 3, characterized in that, The functional filler includes nano-silica and / or nano-aramid fibers functionalized with quadruple hydrogen bonding units.

5. A method for preparing a solid-state battery using vapor-phase lithium replenishment, characterized in that, Used to prepare a solid-state battery as described in any one of claims 1-4; the preparation method includes: The positive electrode, the solid polymer electrolyte layer, and the negative electrode are stacked sequentially in a single-layer battery cell structure of positive electrode-solid polymer electrolyte layer-negative electrode and then packaged in a shell, with the gas phase entering the opening, to obtain the battery assembly to be processed. The solid polymer electrolyte layer includes a polymer containing four hydrogen bond units. The battery assembly to be treated is placed in a gas phase processing chamber. Under an inert atmosphere, a lithium-containing gas phase formed by a lithium replenishment source is supplied to the gas phase processing chamber through a supply device. The lithium-containing gas phase enters the battery assembly to be treated through the gas phase inlet and diffuses to the contact interface between the negative electrode and the solid polymer electrolyte layer to form a lithium-containing interface layer at the contact interface. After the lithium-containing vapor phase treatment is completed, the vapor phase treatment chamber is purged with inert gas, and then the battery assembly to be treated is finally packaged.

6. The method for preparing lithium by gas-phase lithium supplementation according to claim 5, characterized in that, The lithium supplement source is formed into the lithium-containing gas phase through vaporization, sublimation, atomization, and thermal decomposition, or it is formed by being carried by a carrier gas.

7. The method for preparing lithium by gas-phase lithium supplementation according to claim 6, characterized in that, The lithium source includes any one or a mixture of at least two of the following: tert-butyllithium, a complex formed by lithium and a low-boiling-point ether, and low molecular weight lithium carboxylate.

8. The method for preparing lithium by gas-phase lithium supplementation according to claim 7, characterized in that, In the complex formed by lithium and low-boiling-point ether, the low-boiling-point ether includes tetrahydrofuran and / or dimethoxyethane.

9. The method for preparing lithium by gas-phase lithium supplementation according to claim 7, characterized in that, The low molecular weight lithium carboxylate includes lithium formate and / or lithium acetate.

10. The method for preparing lithium by gas-phase lithium supplementation according to claim 7, characterized in that, The lithium replenishing agent source is a tert-butyllithium / pentane solution, which is prepared through the following steps: Under inert gas protection, a lithium metal dispersion was added to pentane, and a reaction solution containing chlorinated n-butane was added dropwise under stirring at 35°C to carry out the reaction and obtain the reactants. The reactants were filtered, washed, and diluted to obtain a 1.0 mol / L tert-butyllithium / pentane solution. In the gas-phase lithium replenishment method, the tert-butyllithium / pentane solution is vaporized, atomized, or carried by a carrier gas to form the lithium-containing gas phase.